EFFORTS TO THE IMPROVEMENT OF BODILY KINESTHETIC INTELLIGENCE OF EARLY CHILDHOOD STUDENTS AT PAUD ADHICITTA THROUGH DANCE MOVEMENTS: UPAYA PENINGKATAN KECERDASAN BADAN KINESTETIK SISWA PENDIDIKAN ANAK USIA DINI ADHICITTA MELALUI GERAKAN TARI - Indriyani, Indriyani; Sukodoyo, Sukodoyo; Endah Ekowati, Wilis Rengganiasih (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2019)
This research aims to determine the successful improvement of the bodily-kinesthetic intelligence of students at PAUD Adhicitta through dance movements. This research is a class action research applying Kemmis & McTaggart model. The research was performed at PAUD Adhicitta Semarang Regency. The research subjects were ten students, and parents. The techniques and data collection instrument included observation, interviews, and documentation. The instruments utilized student and teacher observation sheets. The data analysis of this research applied qualitative and quantitative descriptive analysis techniques. The results showed that the Puja Bakti Kumandang dance movement was very effective to improve the bodily-kinesthetic intelligence of PAUD Adhicitta students. The effectiveness of the results of the study showed an increase in the intelligence of kinesthetic bodies of students from Cycle I to Cycle III. In Cycle I the kinesthetic intelligence of students was 165 and in Cycle II it had increased to 305. In this second cycle, students' kinesthetic body intelligence increased by 84.84%. In Cycle III the intelligence of students' kinesthetic bodies increased to 327 and to put in percentage, it increased 7.21% from Cycle II. The success of the activities undertaken in this study research was influenced by several factors, such as the student’s condition, attendance, dance movements, environment, peers, teachers, and the support of their parents. Penelitian ini bertujuan untuk mengetahui keberhasilan peningkatan kecerdasan badan kinestetik siswa PAUD Adhicitta melalui gerakan tari. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) menggunakan model Kemmis & McTaggart. Penelitian dilakasanakan di PAUD Adhicitta Kabupaten Semarang. Subjek penelitian yaitu sepuluh siswa dan orang tua siswa. Teknik dan instrumen pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Instrumen yang digunakan adalah lembar observasi siswa dan guru. Analisis data pada penelitian ini menggunakan teknik analisis kuantitatif deskriptif dan kualitatif deskriptif. Hasil penelitian menunjukkan bahwa gerakan tari Puja Bakti Kumandang sangat efektif untuk meningkatkan kecerdasan badan kinestetik siswa PAUD Adhicitta. Keefektifan dapat dilihat dari hasil penelitian yang menunjukkan adanya peningkatan kecerdasan badan kinestetik siswa dari Siklus I hingga Siklus III. Pada Siklus I kecerdasan badan kinestetik siswa adalah 165 dan Siklus II mengalami peningkatan menjadi 305. Pada Siklus II ini kecerdasan badan kinestetik siswa mengalami peningkatan sebesar 84,84%. Pada Siklus III kecerdasan badan kinestetik siswa meingkat menjadi 327 dan jika dipersentasikan meningkat 7,21% dari Siklus II. Keberhasilan tindakan yang dilakukan pada penelitian ini dipengaruhi oleh beberapa faktor antara lain kondisi siswa, kehadiran, gerakan tari, lingkungan, teman sebaya, guru, dan dukungan dari orang tua.